Role and regulation of Cdk inhibitors in development and cancer - Roussel, Martine (Henry Stewart Talks, 2009)
Somatic cell cycle, Rb pathway, Positive regulation of G1 phase by phosphorylation of the retinoblastoma protein (Rb) by cyclin-dependent kinases (Cdks), Negative regulation of G1 by Cdk-inhibitory proteins (CKIs), Rb pathway is often disrupted in cancers, Two families of CKIs, differential expression in embryogenesis and adult mouse tissues, Loss of p18Ink4c and p19ink4d induces male sterility, Loss of p19Ink4d induces progressive deafness after birth, Loss of p19Ink4d and p27Kip1 induces re-entry of differentiated postmitotic neurons in cycle after birth, Loss of Ink4c and Patched or p53 induces medulloblastoma, a pediatric tumor of the cerebellum, CKIs are required for exit from and maintenance of cell cycle exit, or quiescence, a reversible state, Loss of CKIs leads to sterility, deafness and cancers